The role of microbiome and metabolomics in personalized ICU nutrition - Herrero, Santiago (Indonesian Nutrition Association, 2025)
Emerging research highlights the essential influence of the gut microbiome and metabolic profiling in managing critically ill patients. In contemporary intensive care units, nutritional support transcends traditional caloric and protein matching; it demands a responsive, multifactorial approach that acknowledges microbial ecology and dynamic metabolic states. These scientific advancements hold promise for redefining nutritional protocols and enhancing patient outcomes in critical care. The gut microbiome, often termed